Characteristics of clinical details and endolymphatic hydrops in unilateral and bilateral Ménière's disease in a single Asian group - Shi, Suming; Li, Wenquan; Wang, Dan; Ren, Tongli; Wang, Wuqing (Frontiers in Neurology, 2022)
Objectives To elucidate the characteristics of the clinical details and endolymphatic hydrops (EH) in bilateral Ménière's disease (BMD). Methods A total of 545 patients with definite MD were enrolled. Demographic variables; the age of onset; disease course; inner ear function; the coexistence of related disorders such as migraine, delayed MD, drop attacks, and autoimmune diseases; familial history; and characteristics of EH were analyzed. Results In the study population, the prevalence of BMD was 15.4%. The disease duration of BMD (84.0 ± 89.6 months) was significantly longer than that of unilateral MD (UMD, 60.1 ± 94.0 months) (P = 0.001). As evaluated by hearing thresholds and cervical and ocular vestibular evoked myogenic potentials, inner ear functions were more deteriorated in BMD (P < 0.05) than in UMD. The proportions of delayed MD and a family history of vertigo were significantly larger in BMD (P < 0.05). EH was observed in 100% of cases on the clinically affected side and 6.1% of cases on the unaffected side. Conclusion A low prevalence of BMD, longer disease duration, higher frequencies of delayed MD, and family history of vertigo in patients with BMD were significant findings observed in the present study. All affected ears presented with EH, and a low percentage of unaffected sides presented with EH.